2021
DOI: 10.1242/jeb.242364
|View full text |Cite
|
Sign up to set email alerts
|

Rapid embryonic development supports the early onset of gill functions in two coral reef damselfishes

Abstract: The gill is one of the most important organs for growth and survival of fishes. Early life stages in coral reef fishes often exhibit extreme physiological and demographic characteristics that are linked to well-established respiratory and ionoregulatory processes. However, gill development and function in coral reef fishes is not well understood. Therefore, we investigated gill morphology, oxygen uptake and ionoregulatory systems throughout embryogenesis in two coral reef damselfishes, Acanthochromis polyacant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Here, we found that, across their entire pelagic stage, larvae of cinnamon anemonefish have among the highest mass-specific oxygen uptake rates (i.e., both SMR and MMR) of any teleost fish species studied to date [ 9 ]. Specifically for anemonefishes and direct developing fishes that are well developed upon hatch [ 26 ], high SMR may be required to support oxygen demands of development and growth of complex tissues (e.g., eyes and brain) [ 26 28 ]. Additionally, anemonefish, specifically cinnamon anemonefish, are capable of swimming—a highly energetically demanding activity—immediately upon hatching, which will add to their metabolic demands.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that, across their entire pelagic stage, larvae of cinnamon anemonefish have among the highest mass-specific oxygen uptake rates (i.e., both SMR and MMR) of any teleost fish species studied to date [ 9 ]. Specifically for anemonefishes and direct developing fishes that are well developed upon hatch [ 26 ], high SMR may be required to support oxygen demands of development and growth of complex tissues (e.g., eyes and brain) [ 26 28 ]. Additionally, anemonefish, specifically cinnamon anemonefish, are capable of swimming—a highly energetically demanding activity—immediately upon hatching, which will add to their metabolic demands.…”
Section: Discussionmentioning
confidence: 99%